Changes in disease activity, disability and mortality of inflammatory arthritis in in the new millennium compared with the 10 years before - He, Mingwei; Wei, Qingjun; Lao, Shan; Lu, William; Chen, Yan (Annals of Joint, 2018)
Inflammatory polyarthritis and its subset rheumatoid arthritis (RA) are characterized by synovial inflammation and hyperplasia, autoantibody production, cartilage and bone destruction, and systemic features, including cardiovascular, pulmonary, psychological, and skeletal disorders (1,2). In contrast to osteoarthritis, which is also associated with cartilage and bone destruction but generally considered as noninflammatory arthritis and with hardly any treatment options that modify the course (3-5), outcomes of inflammatory polyarthritis and RA can be improved by administration of appropriate therapy. Nevertheless, a number of studies comparing changes in the long-term outcome of treatment for patients with inflammatory polyarthritis during the mid-1990s have achieved inconsistent conclusions (6,7). Furthermore, there are suggestions that RA is becoming less severe (8,9). Thus, it would be of interest to investigate whether any improvements in long-term outcome are associated with less severe disease or with the changes in treatment strategy.